Daily physical activity patterns from hip- and wrist-worn accelerometers. (21st September 2016) - Shiroma, E J; Schepps, M A; Harezlak, J; Chen, K Y; Matthews, C E; Koster, A; Caserotti, P; Glynn, N W; Harris, T B
Abstract: Accelerometer wear location may influence physical activity estimates. This study investigates this relationship through the examination of activity patterns throughout the day. Participants from the aging research evaluating accelerometry (AREA) study ( n men  =  37, n women  =  47, mean age (SD)  =  78.9 (5.5) years) were asked to wear accelerometers in a free-living environment for 7 d at three different wear locations; one on each wrist and one on the right hip. During waking hours, wrist-worn accelerometers consistently produced higher median activity counts, about 5  ×  higher, as well as wider variability compared to hip-worn monitors. However, the shape of the accrual pattern curve over the course of the day for the hip and wrist are similar; there is a spike in activity in the morning, with a prolonged tapering of activity level as the day progresses. The similar patterns of hip and wrist activity accrual provide support that each location is capable of estimating total physical activity volume. The examination of activity patterns over time may provide a more detailed way to examine differences in wear location and different subpopulations.